Performance of the Timor-leste democracy consolidation: Analyzing opportunities, challenges and expectations for a more inclusive society - Pereira, Martinho (2022)
The process of democratic consolidation in Timor-Leste is still a recent, associated with the restoration of the independence of the country on 20 may 2002. It is a country that is still young and is facing a very difficult economy, with more than half of the population living in poverty. Meanwhile, the Timorese people show the interest and ability to mobilize to adapt the democratic regime, how best to ensure popular sovereignty in the country's governance. Since independence, Timor-Leste has been making progress in consolidating democracy, in particular by multi-parties and based on the principle of universal suffrage and with a very high electoral participation rate (averaging 80% in all 11 electoral acts, both presidential and legislature election). We intend to analyze the evolution of democratization in Timor-Leste, structured in three stages: (I) political freedom in the decolonization process; (ii) political transition, such as during Indonesian occupation; (iii) and the entry into democracy consolidation initially in the restoration of independence in 2002 to the present day. For this purpose, a mixed methodology will be used, based on the statistics published in the National Commission of Elections Reports, Timor-Leste Strategic Development Plan 2011 – 2030, The Economist Intelligence Unit and Human Development Indices 2018.